2015
DOI: 10.1590/1519-6984.0913
|View full text |Cite
|
Sign up to set email alerts
|

Vascular epiphytes of the Atlantic Forest in the Sinos River basin, state of Rio Grande do Sul, Brazil: richness, floristic composition and community structure

Abstract: The Atlantic Forest, which has a vast epiphytic richness, is a priority area for preservation, listed as one of the five most important world hotspots. Vascular epiphyte richness, composition and community structure were studied in two fragments, one of the ombrophilous (29°43'42"S and 50°22'00"W) and the other of the seasonal (29°40'54"S and 51°06'56"W) forest, both belonging to the Atlantic Forest biome in the Sinos River basin, Rio Grande do Sul, Brazil. In each fragment, 40 trees, divided into four ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
(91 reference statements)
1
5
0
2
Order By: Relevance
“…Sampling four vegetation types resulted in double the number of species compared with de la Rosa- Manzano et al (2017), who only sampled two vegetation types. Overall, the low species richness encountered herein is comparable to that of some subtropical forests (e.g., Atlantic and broadleaf temperate forests; Barbosa, Becker, Cunha, Droste, & Schmitt, 2015;Ceballos, Chacoff, & Malizia, 2016;D ıaz et al, 2010;Hsu et al, 2012;Xu & Liu, 2005) but lower than that of other subtropical forests in the southern hemisphere (e.g., Brown, 1990;Hofstede, Dickinson, & Mark, 2001). This low richness may possibly be due to the decreasing number of species per unit area toward the poles, as observed in coniferous forests (e.g., Khine, 2018).…”
Section: Epiphytic Richness In a Transition Zonesupporting
confidence: 53%
“…Sampling four vegetation types resulted in double the number of species compared with de la Rosa- Manzano et al (2017), who only sampled two vegetation types. Overall, the low species richness encountered herein is comparable to that of some subtropical forests (e.g., Atlantic and broadleaf temperate forests; Barbosa, Becker, Cunha, Droste, & Schmitt, 2015;Ceballos, Chacoff, & Malizia, 2016;D ıaz et al, 2010;Hsu et al, 2012;Xu & Liu, 2005) but lower than that of other subtropical forests in the southern hemisphere (e.g., Brown, 1990;Hofstede, Dickinson, & Mark, 2001). This low richness may possibly be due to the decreasing number of species per unit area toward the poles, as observed in coniferous forests (e.g., Khine, 2018).…”
Section: Epiphytic Richness In a Transition Zonesupporting
confidence: 53%
“…The predominance of this category has been often reported for epiphytic communities in moist subtropical climates (Gonçalves & Waechter 2003;Barbosa et al 2015;Machado et al 2016). Facultative holoepiphytes (HLF) represent a diverse taxonomic group, commonly varying according to the environmental characteristics, such as the abundance of rocky outcrops (walls or boulders) inside or adjacent to forests.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Becker et al (2014) recorded 30 species near the source of the Rio dos Sinos in Caraá, out of which only three were shared with the present study. Barbosa et al (2015), in a study carried out in an urban park in the lower stretch of the basin, recorded only nine species of epiphytic ferns, four of which were shared with this study. This fact may be associated to vegetation and environment characteristics, since epiphytes, especially ferns, need a healthy environment to develop (Johansson, 1974) and Rocha-Uriartt et al (2015) showed that there is a decreasing gradient in vegetation degradation from the source towards the mouth of the river in the RSHB.…”
Section: Floristic Inventory and Community Structurementioning
confidence: 44%